Influencer atau buzzer? analisis efektivitas konten tiktok terhadap brand awareness dan keputusan pembelian impulsif - Livia Irene; Maliana Puspa Arum; Muhammad Eka Purbaya (Jurnal Ilmu Manajemen, 2025)
The development of digital marketing on the TikTok platform has encouraged brands to utilize influencers and buzzers as a promotional strategy that reaches a massive audience. This study aims to analyze the effect of the effectiveness of buzzer and influencer content on brand awareness and its impact on impulse purchases of The Originote products, with brand awareness as a mediating variable. This study uses a quantitative approach through a survey method of 185 female respondents in Central Java who actively use TikTok. Data were collected using a questionnaire and analyzed using Structural Equation Modeling techniques. The results showed that content from influencers and buzzers influenced brand awareness and impulse purchases. Brand awareness is proven to be a mediator in shaping impulse buying decisions. This research contributes to the understanding of content-based marketing strategies on social media and practical implications for companies in optimizing effective digital campaigns.